The relationship of psychological compatibility to the learning impulse of the high school students: Physical education and sport, model - Medjadi, Mostefa; Meliani, Abdelkrim; Bensaid, Mahmoud (Journal of Human Sciences, 2022)
The aim of the study is to know the relationship between the psychological compatibility and the motivation of learning in secondary school students, through the physical and sports education classroom, the study was based on the analytical descriptive curriculum, the sample of 150 students from secondary education was used in the study as a questionnaire tool. Through this study, it became clear that the studied sample achieved moderate levels of psychological harmony among pupils in a second year of secondary education through the physical and sports education classes. In lower-than-motivated levels, learning among students in a second year of secondary education through physical and sports education is evident, and there is a difference in the degrees of psychological and motivational learning by gender.